An investigation on the addition of SrTiO3 to the hydrogen storage properties of the 4MgH2‐Li3AlH6 composite. (2nd February 2022) - Itam Sulaiman, Nurul Nafiqah; Yahya, Muhammad Syarifuddin; Sazelee, Noratiqah; Ali, Nurul Amirah; Mustafa, Nurul Shafikah; Abdul Halim Yap, Muhammad Firdaus Asyraf; Ismail, Mohammad
Summary: The 4MgH2 ‐Li3 AlH6 destabilized system is deemed as a propitious composite to store hydrogen in a solid form. The catalytic effects of strontium titanate (SrTiO3 ) on the hydrogen sorption performances of the 4MgH2 ‐Li3 AlH6 system which was prepared by the ball milling were studied for the first time. It was found that SrTiO3 demonstrates a good catalytic ability to the 4MgH2 ‐Li3 AlH6 system by reducing the onset decomposition temperature as well as enhancing its rehydrogenation kinetics performance. The SrTiO3 /4MgH2 ‐Li3 AlH6 composite has started to release hydrogen at 135°C and 215°C, for the first two steps of desorption, respectively. These temperature values are about 35°C lower for both stages as opposed to the pure 4MgH2 ‐Li3 AlH6 system. In terms of the rehydrogenation kinetics, the composite of SrTiO3 /4MgH2 ‐Li3 AlH6 composite absorbed approximately 4.23 wt% of hydrogen within 30 minutes of adsorption at 320°C. In contrast, the 4MgH2 ‐Li3 AlH6 destabilized system showed a hydrogen adsorption capacity of 3.53 wt% under similar conditions. The inclusion of SrTiO3 to the 4MgH2 ‐Li3 AlH6 system did not result in the enhancement of its desorption kinetics performance at 320°C. The apparent activation energy for the hydrogen desorption of SrTiO3 /4MgH2 ‐Li3 AlH6 composite that was obtained by the Kissinger analysis was calculated to be 119 kJ/mol, which is significantly lower than the pure composite (151 kJ/mol). The images observed by the scanning electron microscopy demonstrated that all the materials are well mixed after the ball milling process and it can be proposed that the key role played by the SrTiO3 was based on the alteration of the microstructure of the composite. From the X‐ray diffraction analysis, it was observed that SrTiO3 is a stable and inert catalyst. Thus, the improvement in the hydrogen sorption performances of the 4MgH2 ‐Li3 AlH6 composite is mainly ascribed to the pulverization effect introduced by SrTiO3 . Abstract : The SrTiO3 /4MgH2‐Li3 AlH6 composite has started to release hydrogen at 135°C and 215°C, for the first two steps of desorption. In terms of the rehydrogenation kinetics, the composite of SrTiO3 /4MgH2 ‐Li3 AlH6 composite absorbed approximately 4.23 wt% of hydrogen within 30 minutes of adsorption at 320°C. The improvement in the hydrogen sorption performances of the 4MgH2 ‐Li3 AlH6 composite is mainly ascribed to the pulverization effect introduced by SrTiO3 as the SrTiO3 in this study is observed to be stable and inert.